Algorithmic Number Theory 9th International Symposium, ANTS-IX, Nancy, France, July 19-23, 2010. Proceedings - Hanrot, Guillaume.; Morain, Franȯis.; Thom,̌ Emmanuel. (Lecture Notes in Computer Science, 2010)
This book constitutes the refereed proceedings of the 9th International Algorithmic Number Theory Symposium, ANTS 2010, held in Nancy, France, in July 2010. The 25 revised full papers presented together with 5 invited papers were carefully reviewed and selected for inclusion in the book. The papers are devoted to algorithmic aspects of number theory, including elementary number theory, algebraic number theory, analytic number theory, geometry of numbers, algebraic geometry, finite fields, and cryptography.